Kepercayaan The Bootstrap Percentile Confidence Interval untuk Koefisien Variasi - Suherman, Alya Salsabilla; Kudus, Abdul (Jurnal Riset Statistika, 2024)
Abstract. The Inverse Gaussian (IG) distribution is used to model data that has a positively skewed or right-skewed distribution. The coefficient of variation (CV) is the ratio of the standard deviation to the mean value. It reflects a good measure of dispersion used when comparing two or more groups of data. One method for estimating the coefficient of variation (CV) confidence interval is The Bootstrap Percentile Confidence Interval (BPCI) method. In this thesis, the BPCI method will be applied to the coefficient of variation of the IG distribution on PM 2.5 air quality data. In the research process, the stages of analysis carried out include calculating the estimated parameters of the IG distribution using the maximum likelihood method, conducting the Kolmogorov-Smirnov fit test, generating data with parameters as estimated and estimating the parameters 1000 times, then calculating the 95% confidence interval with the BPCI method. Based on the calculation results, it is obtained that the PM 2.5 air quality data in Semarang City in 2023 is suitable to be modeled with IG distribution and BPCI confidence interval with 95% confidence level for KV of the data is between the range [0.31 ;0.42]. Abstrak. Distribusi Invers Gaussian (IG) digunakan untuk memodelkan data yang memiliki distribusi kemiringan positif atau condong kekanan. Koefisien variasi (KV) merupakan perbandingan antara standar deviasi dengan nilai rata-rata. KV mencerminkan ukuran penyebaran yang baik digunakan ketika membandingkan dua atau lebih kelompok data. Salah satu metode untuk menaksir selang kepercayaan koefisien variasi (KV) yaitu metode The Bootstrap Percentile Confidence Interval (BPCI). Dalam skripsi ini akan dilakukan penerapan metode BPCI untuk koefisien variasi dari distribusi IG pada data kualitas udara PM 2.5. Dalam proses penelitian tahapan analisis yang dilakukan meliputi menghitung taksiran parameter dari distribusi IG menggunakan metode maksimum likelihood, melakukan uji kecocokan Kolmogorov-Smirnov, membangkitkan data dengan parameter sebagaimana taksirannya dan menaksir parameternya sebanyak 1000 kali, kemudian menghitung selang kepercayaan 95% dengan metode BPCI. Berdasarkan hasil perhitungan diperoleh bahwa data kualitas udara PM 2.5 di Kota Semarang tahun 2023 cocok dimodelkan dengan distribusi IG dan selang kepercayaan BPCI dengan tingkat kepercayaan 95% untuk KV dari data tersebut berada diantara rentang [0,31 ;0,42].